2020
DOI: 10.1111/fog.12463
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term trends and drivers of larval phenology and abundance of dominant brachyuran crabs in the Gulf of St. Lawrence (Canada)

Abstract: Climate change has led to major shifts in the timing of biological events, with many studies demonstrating earlier phenology in response to warming. However, few of these studies have investigated the effects of climate change on the phenology of larvae in marine species. Phenological shifts can result in mismatches between consumers and prey and hence affect growth and survival of individuals, and ultimately population demography. We investigated the temporal changes in phenology and abundance of the larvae o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Altered productivity (Asch, 2015;Cushing, 1975). Subsequent to Asch (2015), incidents of altered phenology have been documented in phytoplankton (Chivers et al, 2020;Salgado-Hernanz et al, 2019), crustaceans (Emond et al, 2020), and fish (Lombardo et al, 2020) in various locations around the world. Within the CCE, anchovy was very abundant during the winter off Oregon even though it had never been observed to spawn in this season, and sardine and hake were much more copious than normal in winter of the MHW (Auth et al, 2018).…”
Section: Phenologymentioning
confidence: 99%
“…Altered productivity (Asch, 2015;Cushing, 1975). Subsequent to Asch (2015), incidents of altered phenology have been documented in phytoplankton (Chivers et al, 2020;Salgado-Hernanz et al, 2019), crustaceans (Emond et al, 2020), and fish (Lombardo et al, 2020) in various locations around the world. Within the CCE, anchovy was very abundant during the winter off Oregon even though it had never been observed to spawn in this season, and sardine and hake were much more copious than normal in winter of the MHW (Auth et al, 2018).…”
Section: Phenologymentioning
confidence: 99%
“…A second possibility is that sea ice processes could operate through ecosystem production and associated match-mismatch phenology of early-life feeding (i.e. [57]), as suggested by [58,59]. Although specific mechanisms of environmental regulation of stock productivity resulting from both sea ice and AO require further research, our research indicates that sea ice has a consistent directional effect on stock productivity while AO has a regionally specific directional role in regulating stocks.…”
Section: Snow Crab Sea Ice Ao and Co 2 Dynamicsmentioning
confidence: 73%
“…Beyond selection of inclusion for specific climate variables to attempt to model snow crab biomass, intrinsic population processes could affect predictive performance of the STPM. For example, within portions of the Gulf of St. Lawrence it has been suggested that pulses of larval abundance are partially moderated through a cohort resonance phenomenon resulting from cannibalism by females and operating on a 7-9 year repeated cycle [58,59].…”
Section: Plos Climatementioning
confidence: 99%
“…Timing of larval release for benthic invertebrates can be triggered by external cues like temperature, light/dark regimes, lunar and tidal cycles, presence of food or a combination of several factors (Thorson 1950). For snow crab, several theories about the cue for hatching have been discussed (Emond et al 2020). Hatching is proposed to be initiated by the presence of senescent phytoplankton settling through the water column, so that hatching overlaps with post-plankton-bloom when diatoms and copepod nauplii are present as prey for the newly hatched crab larvae, thus increasing survival rate (Kruse et al 2007).…”
Section: Discussionmentioning
confidence: 99%